Kontekstualisasi Konsep Keluarga Sakinah pada Keluarga Muslim Palestina di Camp Pengungsian Yordania - Rosadi, Imron; Akbarizan, Akbarizan (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The sakinah family is the ideal marriage destination according to the Koran. Various ways were taken to achieve this goal. However, people understand the concept of the Sakinah family differently. Differences in views on the concept of the sakinah family are also found in the thoughts of experts in the commentator of the Koran. This article is the result of doctrinal law research with historical approach and conceptual approach. The results of this study indicate that the meaning of the sakinah concept cannot be separated from the socio-cultural background of the interpreters. Imam Qurtuby and Ibn Kathir represent the context of fiqh in interpreting the sakinah family. The concept of the sakinah family tends to be interpreted as a process of realizing the biological function of the family. Imam Thabaryy became a specific commentator adding social functions in realizing the Sakinah family not only a biological functio